Understanding multi-domain compact modeling of light-emitting diodes. Issue 1 (1st January 2021) - K R, Shailesh
Abstract: The purpose of this work is to understand the theoretical aspects related to the compact multi-domain (Optical, Electrical and Thermal) modeling of light-emitting diodes (LEDs). Prior studies have already deliberated extensively on modeling LEDs in multiple domains with diverse levels of intricacies. The need for standardized compact multi-domain models of light-emitting diodes is emphasized. The multi-domain theory explained in this work enables potential end-users to create their own compact multi-domain models of LEDs and study their working in different operating conditions. The end-users can create their own compact multi-domain models of LEDs either from experimental data or from electronic-datasheets. The procedure for developing mathematical models of LEDs in multiple domains is demonstrated in this work. The reason behind current control of LEDs is explained using multi-domain modeling theory. In what way the problem of thermal runaway is handled by driving LEDs with constant current is discussed using the concepts of multi-domain theory. Unlike prior models, it is proposed to model forward voltage as a junction temperature controlled voltage source. Optical power and heating power are represented as junction temperature controlled current sources. The importance of thermal metrics in assessing aging and performance levels is also discussed. This work also recommends minimum parameters required for developing multi-domain compact models of LEDs.